CircSEMA4B inhibits the progression of breast cancer by encoding a novel protein SEMA4B-211aa and regulating AKT phosphorylation - Xuehui Wang; Wei Jian; Qifeng Luo; Lin Fang (Cell Death and Disease, 2022)
Abstract PI3K/AKT signaling pathway plays an important role in regulating the tumorigenesis, recurrence, and metastasis of breast cancer (BC). In this study, we discovered a circRNA with protein-coding potential, which we named circSEMA4B. CircSEMA4B could encode a novel protein, SEMA4B-211aa. Both circSEMA4B and SEMA4B-211aa were remarkably downregulated in BC tissues and cell lines. Low expression of circSEMA4B was positively associated with TNM stage, tumor size, lymph node metastasis, and distant metastasis of BC patients. The functional investigation showed that circSEMA4B and SEMA4B-211aa could significantly inhibit the proliferation and migration of BC in vivo and in vitro. Of note, SEMA4B-211aa inhibited the generation of PIP3 by binding to p85, thereby inhibiting the phosphorylation of AKT (Thr308). CircSEMA4B inhibited the phosphorylation of AKT (Ser473) through miR-330-3p/PDCD4 axis. Taken together, circSEMA4B is a novel negative regulator of PI3K/AKT signaling pathway, providing novel mechanistic insights into the underlying mechanisms of BC.